CRITICAL ANALYSIS OF JOSÉ MARQUES DE MELO’S JOURNALISTIC THINKING - Rüdiger, Francisco; Daros, Otávio (Brazilian journalism research, 2020)
A pioneer figure in the field, José Marques de Melo gained justified fame in journalism studies in Brazil, without elaborating upon a systematic reflection on the subject. In this article, we proceed to the rational reconstruction of what would be his journalism theory, in order to develop a critical judgment about its intellectual meaning and epistemological limits. We argue that his ideas are part of what will be referred to here as liberal-developmentalism. In conclusion, we affirm that the lack of greater scientific and intellectual resonance in his work is the result of the incompatibilities and contradictions of this kind of thinking with the historical formation of Brazilian society. Figura pioneira no campo, José Marques de Melo marcou posição nos estudos de jornalismo no Brasil, sem ter pretendido deixar reflexão sistemática a respeito do assunto. Procedemos neste artigo à reconstrução racional do que seria sua teoria do jornalismo para, no fim, emitir juízo crítico sobre seu significado intelectual e seus limites epistemológicos. Argumentamos que suas ideias se enquadram no que se chamará aqui de liberal-desenvolvimentismo. Em conclusão, afirmamos que a falta de maior ressonância científica e intelectual de sua obra é fruto das incompatibilidades e contradições do referido ideário com a formação histórica da sociedade brasileira. Figura pionera en el campo, José Marques de Melo marcó posición en los estudios de periodismo en Brasil, sin haber tenido la intención de elaborar una reflexión sistemática sobre el tema. En este artículo, procedemos a la reconstrucción racional de lo que sería su teoría del periodismo para, al final, emitir un juicio crítico sobre su significado intelectual y sus límites epistemológicos. Argumentamos que sus ideas caen dentro de lo que aquí se llamará liberal-desarrollismo. En conclusión, afirmamos que la falta de mayor resonancia científica e intelectual en su trabajo es resultado de las incompatibilidades y contradicciones de esa idea con la formación histórica de la sociedad brasileña.